Culture Shock And How To Overcome It So You Can Adapt: Case Studies On Summer Courses Program Participants At Rajamangala University Of Technology Krungthep - Hasanah, Faridatul; Mulawarman, Widyatmike Gede; Midiaty, Midiaty; Wardhana, Evi (Faculty of Teacher Training and Education, Mulawarman University, 2023)
The main problem faced by summer courses students is the problem of communication with Thai people, the majority of whom use the Thai language due to cultural differences. Therefore it is necessary to make adjustments in order to communicate effectively. This research was conducted to find out the form of culture shock experienced by the summer courses participants and how they tried to adjust themselves in dealing with this phenomenon. This research is a qualitative research using ethnographic methods, namely research conducted to find out the meaning and form of socio-cultural in a society that has diversity. The results of this study are that the first-time summer courses students experience two aspects of culture shock, namely environmental aspects and social aspects which include language, food, weather and communication with the community around the environment where they live. The effort they make is to keep trying